Can virtual autopsy with postmortem CT improve clinical diagnosis of cause of death? A retrospective observational cohort study in a Dutch tertiary referral centre. Issue 3 (16th March 2018) - Sonnemans, Lianne J P; Kubat, Bela; Prokop, Mathias; Klein, Willemijn M
Abstract : Objective: To investigate whether virtual autopsy with postmortem CT (PMCT) improves clinical diagnosis of the immediate cause of death. Design: Retrospective observational cohort study. Inclusion criteria: inhospital and out-of-hospital deaths over the age of 1 year in whom virtual autopsy with PMCT and conventional autopsy were performed. Exclusion criteria: forensic cases, postmortal organ donors and cases with incomplete scanning procedures. Cadavers were examined by virtual autopsy with PMCT prior to conventional autopsy. The clinically determined cause of death was recorded before virtual autopsy and was then adjusted with the findings of virtual autopsy. Using conventional autopsy as reference standard, we investigated the increase in sensitivity for immediate cause of death, type of pathology and anatomical system involved before and after virtual autopsy. Setting: Tertiary referral centre. Participants: 86 cadavers that underwent conventional and virtual autopsy between July 2012 and June 2016. Intervention: PMCT consisted of brain, cervical spine and chest–abdomen–pelvis imaging. Conventional autopsy consisted of thoracoabdominal examination with/without brain autopsy. Primary and secondary outcome measures: Increase in sensitivity for the immediate cause of death, type of pathology (infection, haemorrhage, perfusion disorder, other or not assigned) and anatomical system (pulmonary, cardiovascular, gastrointestinal, other or not assigned) involved, before and after virtual autopsy. Results: Using PMCT, the sensitivity for immediate cause of death increased with 12% (95% CI 2% to 22%) from 53% (41% to 64%) to 64% (53% to 75%), with 18% (9% to 27%) from 65% (54% to 76%) to 83% (73% to 91%) for type of pathology and with 19% (9% to 30%) from 65% (54% to 76%) to 85% (75% to 92%) for anatomical system. Conclusion: While unenhanced PMCT is an insufficient substitute for conventional autopsy, it can improve diagnosis of cause of death over clinical diagnosis alone and should therefore be considered whenever autopsy is not performed.